Pengaruh Supervisi Kepala Sekolah, Budaya Sekolah, dan Motivasi Kerja terhadap Disiplin Guru di SMKN Kota Banjarmasin - Sanusi, Muhammad Nunu; Aslamiah, Aslamiah; Sulistiyana, Sulistiyana (LP. Ma'arif Janggan Magetan, 2024)
This research aims to analyze the direct and indirect effects of school principal supervision, school culture, and work motivation on teacher discipline at vocational high schools (SMKN) in Banjarmasin City. The study was motivated by preliminary observations indicating a lack of teacher discipline. This quantitative research involved a sample of 234 teachers out of a total of 563, selected through Proportional Random Sampling. Data were collected via questionnaires and analyzed using SPSS. The results showed that school principal supervision, school culture, and work motivation have both direct and indirect effects on teacher discipline. Specifically, the effect of school principal supervision on teacher discipline is 0.283, the effect of school culture is 0.348, the effect of school principal supervision on work motivation is 0.449, and the effect of school culture on work motivation is 0.355. Indirectly, the effect of school principal supervision on teacher discipline through work motivation is 0.111, and the effect of school culture on teacher discipline through work motivation is 0.088. It is recommended that school principals maintain the quality of supervision and a positive school culture while providing relevant professional development programs to sustain teacher discipline and work motivation.